Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe 2 di Beberapa Puskesmas Kabupaten Banyumas - Aji Wibowo, Much Ilham Novalisa; Fitri, Febiana Melisa; Yasin, Nanang Munif; Kristina, Susi Ari; Prabandari, Yayi Suryo (Jurnal Kefarmasian Indonesia, 2021)
Diabetes mellitus (DM) is considered as ”the mother of all diseases" because it causes many complications. Knowing and measuring medication adherence may have a greater effect on DM patients. Several studies in Indonesia used a questionnaire scale to measure adherence, however they do not validate the study population, so it could still be found anomalous correlation analysis between adherence and clinical data even though it measured in the same country and scale. This study measure the adherence level of type 2 diabetes patients, evaluates the validity of the medication adherence scale, and analyze the correlation with the clinical outcome of type 2 diabetes patients in four health centers in Banyumas district. The study uses a cross-sectional design in Prolanis type 2 DM patients of January -April 2020. The adherence is measured by MARS-10, backward-forward translation method followed by content and internal validation. Clinical outcome is evaluated based on fasting blood glucose measurement. The results of the MARS-10 Gregory index analysis showed content validity in the high category (IG ≥ 0.8). The content validity showed the results of 9 questions with the value of r count> r table (n = 30, r table = 0.361). Reliability analysis showed Cronbach's Alpha 0.747> 0.6. The measurement showed 80.3% was adherent patients and 19.3% was non-adherent patients. Correlation analysis showed that there was no significant relationship (p> 0.05) between patient adherence and clinical outcome. Those results showed that type 2 diabetes mellitus patients in 4 health centers were categorized as adherent but not correlated with the clinical outcome. This was enable due to the clinical outcome was simultaneously influenced by several factors: general factors, individual factors, and unpredictable factors.